AYURVEDIC MANAGEMENT OF PSORIASIS (EKAKUSHTA) WITH PANCHAKARMA CHIKITSA - Vijeyta, Singh; Alok Kumar, Srivastava (International Journal of Ayurveda and Pharma Research, 2015)
Psoriasis is a non-infectious chronic relapsing inflammatory skin disease having unknown etiology, characterized by well-defined dry scaly erythematous patches and covered with adherent silvery white scales. The eruption is usually symmetrical and most commonly affects extensor surfaces of elbows, knees, scalp, nails and the sacral regions. Its incidence is 1-2% of world population. Psychological stress is emphasized as one of the major triggering factor in the exacerbation of the disease. Modern medical science treats psoriasis with PUVA and corticosteroids. But these therapies give serious side effects like hepato & nephrotoxicity, bone marrow depletion etc. Hence it is the need of time to find out safe and effective treatment for Psoriasis and here Ayurveda plays an important role. In Ayurveda, Psoriasis can be correlated with Ekakustha due to very much similarity in their symptoms. The unique treatment modality of Ayurveda provides long lasting results and a better life to patients through its three basic principles of treatment i.e. Shodhana, Shamana and Nidana Parivarjana. Panchakarma (Shodhana) therapy is a unique type of treatment for various chronic, auto-immune, hormonal, degenerative disorders etc, where other sorts of treatments have no satisfactory answer as well equally beneficial for the promotion and preservation of health. In addition of the Shamana Yoga & External Application (Lepan Chikitsa) of drugs is administered after taking the proper course of Shodhana then it provides additional relief and thus helps in eradication of the diseases (psoriasis) completely. The present article reviews the concept of psoriasis in Ayurveda and role of Panchakarma & Shaman Chikitsa in the management of psoriasis.